PENGARUH KEMAMPUAN DAN KOMPENSASI TERHADAP KINERJA KARYAWAN PADA TOKO BANGUNAN MUDA JAYA - Ayu Marviani; Taufik Bustami (Jurnal Entrepreneur dan Manajemen Sains (JEMS), 2023)
This study aims to determine The Effect of Ability on Employee Performance at The Muda Jaya Building Shop, Bukittinggi city either partially or simultaneously. There are several factors that will examined in this study, including Ablility (X1), Compensation (X2). The object of research this time were all employess of The Muda Jaya Building Shop consisting of 37 people. In this study the authors used the data collection method by means of observation and distributing questionners. There are several data analysis techniques used in this study, including using instrument tests, classical assumption tests, analysis of respondent’s responses, multiple linear regression analysis, determinant ceofficients and hypothesis testing. From the result of the multiple linear regression test, the regression equation is : Y = 22.808 + 0.511 (X1) + 0.069 (X2) . The result of the t test on the capability variable (X1) show tcount>ttable (2.529>1.687) , and on the compensation variabele (X2) show tcount<ttable (0.357<1.687) . The results of the f test on the ability variable (X1) and the compensation variable (X2) show fcount>ftable (3.285>3.28). So from the results of the test that have been done it can be concluded that the Capability Variable (X1) and the Compensation Variable (X2) have an effect on Employee performance at The Muda Jaya Building Shop. Key Word : Capability, Compensation, and Employee Performance